Therapy, Pain & Training - Kobel S; Kirsten J; Kelso A (Deutsche Zeitschrift für Sportmedizin)
Anthropometric measurements are non-invasive and easily obtained measurements with a wide range of utility in both paediatric and adult populations, including athletes. They can be used to diagnose risk factors, enhance performance and help patients to assess improvement after treatment. To enhance long-term patient outcomes, an inter-professional team should work together to consistently obtain reproducible results that apply to clinical settings. Accurate serial measurements over time are the most important aspect of anthropometry for a reliable indicator of risk factors. This will help identify at-risk individuals early, help promote a healthy lifestyle, and enhance performance in athletes. Choosing the appropriate assessment method depends on aim, resources, population, and required accuracy.Key Words: BMI, Skinfolds, Ultrasound, Waist-to-Height-Ratio (WHtR), Waist Circumference